Role of Exopolysaccharides of Pseudomonas in Heavy Metal Removal and Other Remediation Strategies - Balíková, Katarína; Vojtková, Hana; Duborská, Eva; Kim, Hyunjung; Matúš, Peter; Urík, Martin (Polymers, 2022)
Pseudomonas biofilms have been studied intensively for several decades and research outcomes have been successfully implemented in various medical and agricultural applications. Research on biofilm synthesis and composition has also overlapped with the objectives of environmental sciences, since biofilm components show exceptional physicochemical properties applicable to remediation techniques. Especially, exopolysaccharides (ExPs) have been at the center of scientific interest, indicating their potential in solving the environmental issues of heavy metal land and water contamination via sorptive interactions and flocculation. Since exposure to heavy metal via contaminated water or soil poses an imminent risk to the environment and human health, ExPs provide an interesting and viable solution to this issue, alongside other effective and green remedial techniques (e.g., phytostabilization, implementation of biosolids, and biosorption using agricultural wastes) aiming to restore contaminated sites to their natural, pollution-free state, or to ameliorate the negative impact of heavy metals on the environment. Thus, we discuss the plausible role and performance of Pseudomonas ExPs in remediation techniques, aiming to provide the relevant available and comprehensive information on ExPs' biosynthesis and their usage in heavy metal remediation or other environmental applications, such as wastewater treatment via bioflocculation and soil remediation.
Keywords: exopolysaccharides; bioremediation; biosorption; Pseudomonas; heavy metals